TEACHER CLASS MANAGEMENT ABILITY IN IMPROVING SCHOOL QUALITY - Sabaruddin Sabaruddin; Muhammad Sapril Siregar (Jurnal Maritim Malahayati, 2021)
The purpose of this study was to determine the ability of teachers in managing the classroom to improve quality. This study uses a qualitative approach. Data collection techniques are: interviews, observations, and documentation studies. Data analysis techniques with data reduction, displaying data, drawing conclusions and verification. The subjects of this study were 1 principal and 15 BP2IP teachers at Malahayati School Aceh. Based on the results of the study, it is known that: the leadership of the principal and the ability of teacher class management in improving the quality of BP2IP Malahayati Aceh's schools has been going well, although not optimally. There are still shortcomings that must be corrected by the BP2IP Malahayati Aceh School Teacher.